Prediction of Vitamin K Response Using the Echis Time and Echis-Prothrombin Time Ratio - Solano, C; Cobcroft, R G; Scott, D C (Thrombosis and Haemostasis, 1990)
Echis carinatus venom contains proteases capable of activating both normal and descarboxy prothrombin. We showed this venom (Sigma) principally activates prothrombin with almost no factor X activation. Echis time in combination with prothrombin time can predict vitamin K responsiveness since the Echis time is usually normal in the presence of descarboxy prothrombin associated with vitamin K deficiency.38 patients with abnormal routine prothrombin times (PT) had both coagulant and immunogenic factor II assays along with Echis times done before and after vitamin K. Of 22 patients responding to vitamin K, based on correction of PT, 21 had normal initial Echis times and of 16 not responding, 11 had abnormal Echis times, giving a sensitivity of 95.4% and specificity of 68.8% for vitamin K responsiveness. 90% of patients with a PT/Echis time ratio <1.3 and a prolonged Echis time did not correct their PTs with vitamin K therapy.The 5 non-responders with normal Echis times all showed normal initial coagulant and antigenic prothrombin, but 3 had low F V and/or F VII.